A Current Review of the Diagnostic and Treatment Strategies of Hepatic Encephalopathy - Z. Poh; P. E. J. Chang (International Journal of Hepatology)
Hepatic encephalopathy (HE) is a serious and potentially fatal complication in patients with cirrhotic liver disease. It is a spectrum ranging from minimal hepatic encephalopathy (MHE) without recognizable clinical symptoms or signs, to overt HE with risk of cerebral edema and death. HE results in diminished quality of life and survival. The broad range of neuropsychiatric manifestations reflects the range of pathophysiological mechanisms and impairment in neurotransmission that are purported to cause HE including hyperammonemia, astrocyte swelling, intra-astrocytic glutamine, upregulation of 18-kDa translocator protein (TSPO) (formerly known as peripheral benzodiazepine receptor or PBTR), and manganese. There is a myriad of diagnostic tools including simple bedside clinical assessment, and more complex neuropsychological batteries and neurophysiological tests available today. Current treatment strategies are directed at reducing ammonia, with newer agents showing some early promise. This paper describes the pathophysiology of the disease and summarises current diagnostic and treatment therapies available.